Creative spaces for qualitative researching living research - Higgs, Joy; Titchen, Angie; Horsfall, Debbie; Bridges, Donna (Practice, education, work and society, 2011)
Creative Spaces for Qualitative Researching: Living Research. This book looks inward at researchers who are seeking to live their research {u2013} to embody the principles, methodologies and ethical conduct that comprises their research strategies. And, it looks outward at the living world as the focus of qualitative research. From both perspectives the editors and authors of this book have created spaces for qualitative research that provide critical and creative frameworks for conducting and living their research. A rich variety of research voices and lives are illuminated, liberated and revealed in the book. There are five sections in the book: Researching Living Practices Doing Creative Research Being a Creative Researcher Co-Creating Qualitative Research in Creative Spaces Becoming Transformed Through Creative Research.